Renal Artery Blood Flow and Surface Parenchymal Perfusion During Renal Artery Endoshunting in a Porcine Model - Johan Millinger; Marcus Langenskiöld; Andreas Nygren; Klas Österberg; Joakim Nordanstig (EJVES Vascular Forum)
Objective: Ischaemia and reperfusion can result in permanent tissue damage. During complex open abdominal aortic surgery, transient clamping of the renovisceral arteries may be required to successfully complete the vascular repair. Endovascular shunting (endoshunting) presents an alternative technique for managing such temporary renovisceral ischaemia. This study aimed to investigate the performance of endoshunting to the renal circulation in a porcine model. Methods: This study of five domestic pigs investigated arterial volume flow rates during endoshunting of a single renal artery and the associated impact on renal perfusion parameters (laser Doppler renal parenchymal perfusion, renal oxygen extraction, and selective urinary output). The study was performed in three steps: baseline registrations (30 minutes), endoshunting (120 minutes), and restoration (60 minutes). The right kidney was used as the experimental side and the left kidney as control. Results: The median arterial flow rate in the left control kidney remained constant throughout the experiment. On the right (endoshunted) side, the baseline median arterial flow rate was 267 (range, 160–404) mL/min. Following activation of the endoshunt, the median arterial volume flow dropped by 59%–110 (range, 45–150) mL/min (p = .018). During endoshunting, the median kidney surface perfusion decreased to 42% of the baseline value. On the control side, a rise in the median parenchymal perfusion was observed after endoshunt activation, which was again normalised following restoration of native right renal artery flow. During endoshunting, the median regional urine production was 0.32 (range, 0.12–0.50) mL/hour but resumed after renal artery flow restoration. Conclusion: On average, the endoshunted kidneys showed a rapid restoration of blood flow, parenchymal perfusion, and urine production after 120 minutes of endoshunting. This suggests that endoshunting to the kidney using an endoshunt system might be a promising strategy to preserve renal function when temporary interruption of native renal artery blood flow is needed during complex vascular surgical repairs involving the renal arteries.